PELATIHAN TEKNIK SIMAK ULANG UCAP DALAM MEMBACA RAWI MAULID NABI DI DESA SINDANGSARI - Sendi Saputra; Irham Irham; Rabianur Rabianur; Acep Mulyadi (LPPM Universitas Islam 45, 2023)
The reading of rawi's birthday of the prophet has become a religious tradition known by the people of Sindangsari village. Usually the recital of the Prophet's birthday is held in a series of activities to welcome the birth of children, baby haircuts, aqiqah, weddings, circumcisions and celebrations of Islamic holidays. In fact, many religious educators in Sindangsari Village, especially in RT 02 RW 05 Kampung Pulo Landak, have not been able to train the community and youth in reading the Prophet's Birthday. Under these conditions, the researcher will train with “simak ulang ucap” technique. The purpose of the training in “simak ulang ucap” technique is to speed up and position the community in reading the rawi of the Prophet's birthday. Also because the rawi maulid book is a book that uses Arabic, the technique of “simak ulang ucap” is part of the method so that there are no mistakes in reading it. The training activity of “simak ulang ucap” technique in reading narrators of the Prophet's birthday was held in several meetings until the quality of reading ability was as expected by the researcher.